2014
DOI: 10.1007/s12264-013-1426-8
|View full text |Cite
|
Sign up to set email alerts
|

A modified light-dark box test for the common marmoset

Abstract: The common marmoset (Callithrix jacchus) has attracted extensive attention for use as a non-human primate model in biomedical research, especially in the study of neuropsychiatric disorders. However, behavioral test methods are still limited in the field of marmoset research. The light-dark box is widely used for the evaluation of anxiety in rodents, but little is known about light-dark preference in marmosets. Here, we modified the light-dark test to study this behavior. The modified apparatus consisted of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In the present study, we found that, through receiving visual inputs from an asymmetrical pathway comprising a specific subset of retinal ganglion cells (RGCs) and eminentia thalami (EmT), the left dHb (L-dHb) in larval zebrafish mediates light-preference behavior, which is a highly conserved innate behavior throughout the animal kingdom and crucial for animal survival (Crozier and Pincus, 1927;Gong et al, 2010;Steenbergen et al, 2011;Wang et al, 2014;Ward et al, 2008;Yamanaka et al, 2013). Lesion or dysfunction of the L-dHb, but not right dHb (R-dHb), severely impaired retinal input-dependent lightpreference behavior, while optogenetic activation of L-dHb neurons endowed eye-removed zebrafish with preference capability.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the present study, we found that, through receiving visual inputs from an asymmetrical pathway comprising a specific subset of retinal ganglion cells (RGCs) and eminentia thalami (EmT), the left dHb (L-dHb) in larval zebrafish mediates light-preference behavior, which is a highly conserved innate behavior throughout the animal kingdom and crucial for animal survival (Crozier and Pincus, 1927;Gong et al, 2010;Steenbergen et al, 2011;Wang et al, 2014;Ward et al, 2008;Yamanaka et al, 2013). Lesion or dysfunction of the L-dHb, but not right dHb (R-dHb), severely impaired retinal input-dependent lightpreference behavior, while optogenetic activation of L-dHb neurons endowed eye-removed zebrafish with preference capability.…”
Section: Introductionmentioning
confidence: 94%
“…Light/dark preference is an evolutionarily conserved innate behavior that is found throughout the animal kingdom (Crozier and Pincus, 1927;Gong et al, 2010;Steenbergen et al, 2011;Wang et al, 2014;Ward et al, 2008;Yamanaka et al, 2013). Exposure to an environment with favorable illuminance ecologically helps the animal to forage for food, avoid predators, find conspecifics, and perform courtship behaviors (Navara and Nelson, 2007).…”
Section: Novel Function Of Mhb In Light-preference Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, rodents tend to stay in the dark, but their exploratory behaviour drives them to the light box. Therefore, the increase in the number and time of activities in the light box can reflect a reduction in animal anxiety (29,30). Using the reliable behavioural evaluation system mentioned previously, we effectively screened 17.5 mg/kg as the optimal anti-anxiety effective intervention dose in mice treated with different doses of paeonol.…”
Section: Mg/kg Paeonol Is the Optimal Dosage Against Anxietymentioning
confidence: 99%
“…Optogenetic activation of the left-dorsal habenula (see Fig. 4 b, section D) in eye-removed zebrafish larvae triggers innate light-preference behaviour in zebrafish larvae (Zhang et al 2017 )., This behaviour is critical for survival and highly conserved (Crozier and Pincus 1927 ; Gong et al 2010 ; Steenbergen et al 2011 ; Wang et al 2014 ; Ward et al 2008 ; Yamanaka et al 2013 ; Zhang et al 2017 ).…”
Section: The Teleost Brainmentioning
confidence: 99%